Produção de quitosanase por aspergillus ochraceus em cultivo descontínuo submerso - Silva Filho, Raimundo Cosme da (2005)
In this work a 24 factorial design with triplicate at central point was used in order to investigate the influence of chitosan concentration (substrate) (Cs), culture media temperature (CMT), aeration ratio (AR) as well as agitation (A) on chitosanase production by Aspergillus ochraceus. Experiments were carried out using the following levels to the factors: (Cs) (-1) 0.1%; (0) 0.15%; (+1) 0.2%; (TMC) (-1) 25 minutes; (0) 30 minutes; (+1) 35 minutes; (RA) (-1) 0.4; (0) 0.6; (+1) 0.8; (A) (-1) 90 rpm, (0) 120 rpm, (+1) 150 rpm. One chitosanolytic activity (U.mL-1) was defined as the enzyme necessary to produce 1.0 mmol.min-1 of glicosamine by mL of extract. Chitosanolytic assays were carried out using two extract volumes, 0.05 and 0.1 mL, respectively. Results showed that was possible to produce chitosanase of order aproximatelly 5,9 U.mL-1 by Aspergillus ochraceus and chitosanolytic activity was increased by increment on substrate concentration, aeration ratio as well as agitation while media culture temperature increment decreased activity